Changes of MRI in inter-spinal distraction fusion for lumbar degenerative disease: A retrospective analysis covering 3 years. (November 2020) - Wang, Ruideng; Ji, Xiang; Liu, Lijia; Chen, Hao; Jia, Pu; bao, Li; Feng, Fei; Tang, Hai
Highlights: Inter-spinal distraction and fusion (ISDF) has been a treatment of lumbar disc herniation in recent years as a new type of minimally invasive treatment. It could reduce the damage of lumbar bone tissue, retain the intervertebral disc, and retain posterior column structure of the spine as much as possible. It could relieve clinical symptoms and expanse the spinal canal area in MRI. During 3-year observation, it could partially retract the herniated disc and make it possible to repaire the disc. Abstract: Objective: To assess the preoperative and postoperative changes in MRI image and the short-term efficacy of the ISDF with BacFuse covering 3 years. Methods: 32 patients who underwent ISDF were involved in this retrospective study. The symptoms assessment including VAS, ODI, and SF-12 were evaluated preoperative and postoperative at 1 year and 3 years. The X-ray was used to measure posterior disk height (PDH), foramina height (FH), foramina width (FW), and MRI was taken to assess the cross-sectional area of dura sac (CSADS), cross-sectional area of canal (CSAC), herniated disc area, ligamentum flavum area. The preoperative ratio of herniated disc area and ligamentum flavum area to CSAC were compared with post-operative ratio. The modified Pfirrmann grade system was used to assess the surgical lumbar disc. Results: The symptom indexes were significantly improved after surgery. PDH and FH increased significantly ( P < 0.05) after surgery compared with that before surgery, but there was no statistical difference in FW ( P > 0.05). CSADS and CSAC increased obviously ( P < 0.05), while the area of herniated disc and ligamentum flavum decreased significantly ( P < 0.05). The ratio changes showed a significant difference between last follow-up and pre-operation ( P < 0.05), but there was no statistical significance in grade changes of surgical disc. Conclusion: ISDF with BacFuse could relieve clinical symptoms and expanse the spinal canal area in MRI. During 3-year observation, it could provide continuous traction and maintain the area of spinal canal, so as to partially retract the herniated disc and make it possible to repair the disc.